NCERT Solutions for Class 12 Maths Chapter 1 – Relations and Functions Ex 1.3
Page No 18:
Question 1:
Let f: {1, 3, 4} → {1, 2, 5} and g: {1, 2, 5} → {1, 3} be given by f = {(1, 2), (3, 5), (4, 1)} and g = {(1, 3), (2, 3), (5, 1)}. Write down gof.
Answer:
The functions f: {1, 3, 4} → {1, 2, 5} and g: {1, 2, 5} → {1, 3} are defined as
f = {(1, 2), (3, 5), (4, 1)} and g = {(1, 3), (2, 3), (5, 1)}.
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6045/Chapter%201_html_57f3b03d.gif)
Question 2:
Let f, g and h be functions from R to R. Show that
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6048/Chapter%201_html_m59307f71.gif)
Answer:
To prove:
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6048/Chapter%201_html_4bfa0242.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6048/Chapter%201_html_566b6382.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6048/Chapter%201_html_m4f3371b3.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6048/Chapter%201_html_m715a924e.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6048/Chapter%201_html_m377bec3b.gif)
Question 3:
Find gof and fog, if
(i) ![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6050/Chapter%201_html_5f375722.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6050/Chapter%201_html_5f375722.gif)
(ii) ![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6050/Chapter%201_html_m2242302d.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6050/Chapter%201_html_m2242302d.gif)
Answer:
(i) ![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6050/Chapter%201_html_5f375722.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6050/Chapter%201_html_5f375722.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6050/Chapter%201_html_mc9dd7a9.gif)
(ii) ![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6050/Chapter%201_html_m2242302d.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6050/Chapter%201_html_m2242302d.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6050/Chapter%201_html_m1498fc9.gif)
Question 4:
If
, show that f o f(x) = x, for all
. What is the inverse of f?
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6054/Chapter%201_html_m2c54b729.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6054/Chapter%201_html_m39253282.gif)
Answer:
It is given that
.
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6054/Chapter%201_html_m2c54b729.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6054/Chapter%201_html_m196322d8.gif)
Hence, the given function f is invertible and the inverse of f is f itself.
Question 5:
State with reason whether following functions have inverse
(i) f: {1, 2, 3, 4} → {10} with
f = {(1, 10), (2, 10), (3, 10), (4, 10)}
(ii) g: {5, 6, 7, 8} → {1, 2, 3, 4} with
g = {(5, 4), (6, 3), (7, 4), (8, 2)}
(iii) h: {2, 3, 4, 5} → {7, 9, 11, 13} with
h = {(2, 7), (3, 9), (4, 11), (5, 13)}
Answer:
(i) f: {1, 2, 3, 4} → {10}defined as:
f = {(1, 10), (2, 10), (3, 10), (4, 10)}
From the given definition of f, we can see that f is a many one function as: f(1) = f(2) = f(3) = f(4) = 10
∴f is not one-one.
Hence, function f does not have an inverse.
(ii) g: {5, 6, 7, 8} → {1, 2, 3, 4} defined as:
g = {(5, 4), (6, 3), (7, 4), (8, 2)}
From the given definition of g, it is seen that g is a many one function as: g(5) = g(7) = 4.
∴g is not one-one,
Hence, function g does not have an inverse.
(iii) h: {2, 3, 4, 5} → {7, 9, 11, 13} defined as:
h = {(2, 7), (3, 9), (4, 11), (5, 13)}
It is seen that all distinct elements of the set {2, 3, 4, 5} have distinct images under h.
∴Function h is one-one.
Also, h is onto since for every element y of the set {7, 9, 11, 13}, there exists an element x in the set {2, 3, 4, 5}such that h(x) = y.
Thus, h is a one-one and onto function. Hence, h has an inverse.
Question 6:
Show that f: [−1, 1] → R, given by
is one-one. Find the inverse of the function f: [−1, 1] → Range f.
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6059/Chapter%201_html_m6a332d46.gif)
(Hint: For y ∈Range f, y =
, for some x in [−1, 1], i.e.,
)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6059/Chapter%201_html_m3252a6d5.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6059/Chapter%201_html_m51a30695.gif)
Answer:
f: [−1, 1] → R is given as![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6059/Chapter%201_html_735b2aef.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6059/Chapter%201_html_735b2aef.gif)
Let f(x) = f(y).
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6059/Chapter%201_html_2b620184.gif)
∴ f is a one-one function.
It is clear that f: [−1, 1] → Range f is onto.
∴ f: [−1, 1] → Range f is one-one and onto and therefore, the inverse of the function:
f: [−1, 1] → Range f exists.
Let g: Range f → [−1, 1] be the inverse of f.
Let y be an arbitrary element of range f.
Since f: [−1, 1] → Range f is onto, we have:
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6059/Chapter%201_html_m6dada837.gif)
Now, let us define g: Range f → [−1, 1] as
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6059/Chapter%201_html_7466b8c7.gif)
∴gof =
and fog = ![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6059/Chapter%201_html_m386cf7c4.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6059/Chapter%201_html_2819068d.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6059/Chapter%201_html_m386cf7c4.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6059/Chapter%201_html_4dd19828.gif)
⇒ ![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6059/Chapter%201_html_57eb3e9.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6059/Chapter%201_html_57eb3e9.gif)
Question 7:
Consider f: R → R given by f(x) = 4x + 3. Show that f is invertible. Find the inverse of f.
Answer:
f: R → R is given by,
f(x) = 4x + 3
One-one:
Let f(x) = f(y).
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6060/Chapter%201_html_m761b1178.gif)
∴ f is a one-one function.
Onto:
For y ∈ R, let y = 4x + 3.
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6060/Chapter%201_html_4195f8f1.gif)
Therefore, for any y ∈ R, there exists
such that
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6060/Chapter%201_html_60a29e0a.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6060/Chapter%201_html_m6d747ee9.gif)
∴ f is onto.
Thus, f is one-one and onto and therefore, f−1 exists.
Let us define g: R→ R by
.
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6060/Chapter%201_html_1d7c51d1.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6060/Chapter%201_html_18a30fb0.gif)
∴![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6060/Chapter%201_html_m7e9141ec.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6060/Chapter%201_html_m7e9141ec.gif)
Hence, f is invertible and the inverse of f is given by
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6060/Chapter%201_html_2a2d1bb7.gif)
Question 8:
Consider f: R+ → [4, ∞) given by f(x) = x2 + 4. Show that f is invertible with the inverse f−1 of given f by
, where R+ is the set of all non-negative real numbers.
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6061/Chapter%201_html_2a333a87.gif)
Answer:
f: R+ → [4, ∞) is given as f(x) = x2 + 4.
One-one:
Let f(x) = f(y).
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6061/Chapter%201_html_m7cfa4fd1.gif)
∴ f is a one-one function.
Onto:
For y ∈ [4, ∞), let y = x2 + 4.
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6061/Chapter%201_html_506595d.gif)
Therefore, for any y ∈ R, there exists
such that
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6061/Chapter%201_html_m4518fcda.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6061/Chapter%201_html_1774a55e.gif)
∴ f is onto.
Thus, f is one-one and onto and therefore, f−1 exists.
Let us define g: [4, ∞) → R+ by,
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6061/Chapter%201_html_2c94539a.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6061/Chapter%201_html_m31641b49.gif)
∴![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6061/Chapter%201_html_m1c8142f3.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6061/Chapter%201_html_m1c8142f3.gif)
Hence, f is invertible and the inverse of f is given by
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6061/Chapter%201_html_55a4df99.gif)
Page No 19:
Question 9:
Consider f: R+ → [−5, ∞) given by f(x) = 9x2 + 6x − 5. Show that f is invertible with
.
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6065/Chapter%201_html_m6578c33e.gif)
Answer:
f: R+ → [−5, ∞) is given as f(x) = 9x2 + 6x − 5.
Let y be an arbitrary element of [−5, ∞).
Let y = 9x2 + 6x − 5.
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6065/Chapter%201_html_m61e2d07d.gif)
∴f is onto, thereby range f = [−5, ∞).
Let us define g: [−5, ∞) → R+ as![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6065/Chapter%201_html_m52e3184b.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6065/Chapter%201_html_m52e3184b.gif)
We now have:
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6065/Chapter%201_html_md23d7aa.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6065/Chapter%201_html_46d51344.gif)
∴
and![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6065/Chapter%201_html_m5eafb379.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6065/Chapter%201_html_28d7b353.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6065/Chapter%201_html_m5eafb379.gif)
Hence, f is invertible and the inverse of f is given by
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6065/Chapter%201_html_m19f5c246.gif)
Question 10:
Let f: X → Y be an invertible function. Show that f has unique inverse.
(Hint: suppose g1 and g2 are two inverses of f. Then for all y ∈ Y,
fog1(y) = IY(y) = fog2(y). Use one-one ness of f).
Answer:
Let f: X → Y be an invertible function.
Also, suppose f has two inverses (say
).
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6068/Chapter%201_html_7f5d1628.gif)
Then, for all y ∈Y, we have:
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6068/Chapter%201_html_36b3004b.gif)
Hence, f has a unique inverse.
Question 11:
Consider f: {1, 2, 3} → {a, b, c} given by f(1) = a, f(2) = b and f(3) = c. Find f−1 and show that (f−1)−1 = f.
Answer:
Function f: {1, 2, 3} → {a, b, c} is given by,
f(1) = a, f(2) = b, and f(3) = c
If we define g: {a, b, c} → {1, 2, 3} as g(a) = 1, g(b) = 2, g(c) = 3, then we have:
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6072/Chapter%201_html_m6c2426fc.gif)
∴
and
, where X = {1, 2, 3} and Y= {a, b, c}.
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6072/Chapter%201_html_m2d002022.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6072/Chapter%201_html_m2a3edc62.gif)
Thus, the inverse of f exists and f−1 = g.
∴f−1: {a, b, c} → {1, 2, 3} is given by,
f−1(a) = 1, f−1(b) = 2, f-1(c) = 3
Let us now find the inverse of f−1 i.e., find the inverse of g.
If we define h: {1, 2, 3} → {a, b, c} as
h(1) = a, h(2) = b, h(3) = c, then we have:
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6072/Chapter%201_html_6a6a33b2.gif)
∴
, where X = {1, 2, 3} and Y = {a, b, c}.
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6072/Chapter%201_html_3c64248.gif)
Thus, the inverse of g exists and g−1 = h ⇒ (f−1)−1 = h.
It can be noted that h = f.
Hence, (f−1)−1 = f.
Question 12:
Let f: X → Y be an invertible function. Show that the inverse of f−1 is f, i.e.,
(f−1)−1 = f.
Answer:
Let f: X → Y be an invertible function.
Then, there exists a function g: Y → X such that gof = IXand fog = IY.
Here, f−1 = g.
Now, gof = IXand fog = IY
⇒ f−1of = IXand fof−1= IY
Hence, f−1: Y → X is invertible and f is the inverse of f−1
i.e., (f−1)−1 = f.
Question 13:
If f: R → R be given by
, then fof(x) is
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6075/Chapter%201_html_m49ce42ca.gif)
(A)
(B) x3 (C) x (D) (3 − x3)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6075/Chapter%201_html_m3aeac40c.gif)
Answer:
f: R → R is given as
.
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6075/Chapter%201_html_m49ce42ca.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6075/Chapter%201_html_25362c5e.gif)
The correct answer is C.
Question 14:
Let
be a function defined as
. The inverse of f is map g: Range![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_m4ca863d4.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_3751b097.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_m354ab145.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_m4ca863d4.gif)
(A)
(B) ![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_9e09296.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_m3af6d2ec.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_9e09296.gif)
(C)
(D) ![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_29a6289f.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_m1ab068e3.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_29a6289f.gif)
Answer:
It is given that![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_341935bb.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_341935bb.gif)
Let y be an arbitrary element of Range f.
Then, there exists x ∈
such that ![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_m4786a736.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_3e4b1502.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_m4786a736.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_6a72f987.gif)
Let us define g: Range
as![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_m59b54d57.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_m7f2eeed8.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_m59b54d57.gif)
Now,![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_3a8779b5.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_3a8779b5.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_5420ebc8.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_m10d6f44e.gif)
∴![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_1f2105c2.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_1f2105c2.gif)
Thus, g is the inverse of f i.e., f−1 = g.
Hence, the inverse of f is the map g: Range
, which is given by
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_m7f2eeed8.gif)
![](https://img-nm.mnimgs.com/img/study_content/curr/1/12/15/230/6076/Chapter%201_html_m59b54d57.gif)
The correct answer is B.